Exome sequencing identifies a FHOD3 p.S527del mutation in a Chinese family with hypertrophic cardiomyopathy. (14th January 2020) - Huang, Suqiu; Pu, Tian; Wei, Wei; Xu, Rang; Wu, Yurong
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is the most common inheritable cardiac disease and is characterised by unexplained ventricular myocardial hypertrophy. HCM is highly heterogeneous and is primarily caused by the mutation of genes encoding sarcomere proteins. As a result of its genetic basis, we investigated the underlying cause of HCM in a Chinese family by whole‐exome sequencing. Methods: Whole‐exome sequencing was performed for seven clinically diagnosed HCM family members and the resulting single nucleotide variants associated with cardiac hypertrophy or heart development were analysed by a polymerase chain reaction and Sanger sequencing. Results: A non‐frameshift deletion mutation (p.S527del) of Formin Homology 2 Domain Containing 3 ( FHOD3 ) was detected in all of the affected family members and was absent in all unaffected members, with the exception of one young member. Moreover, three single nucleotide variants associated with heart development and morphogenesis were identified in the proband but were absent in the other affected subjects. Conclusions: This is the first HCM family case of FHOD3 (p.S527del) variation in Asia. Additionally, RNF207 (p.Q268P), CCM2 (p. E233K) and SGCZ (p.Q134X) may be related to the clinical heterogeneity of the family. The present study could enable the provision of genetic counseling for this family and provide a basis for future genetic and functional studies.